Comparison of early and late removal of the urinary catheter after rectal cancer surgery - CİCİBOĞA, KAAN (My University, 2024)
Objective: This study is aiming to compare the results of early and late removal of urinary catheters after rectal cancer surgery. Materials and methods: Patients who undergone rectal cancer surgery in a single center were included in this prospective randomized study. The timing of the urinary catheter removal was randomized by a computer-assisted program and divided into 2 groups, which are early (first 48 h) and late (after 48 h). The primary outcome of this study was to compare the urinary retention and re-catheterization rates between patients with early and those with late catheter removal. Results: Sixty-six patients were included in this study. The median age was 60 (31-88 years), and the patient group was predominantly male (n: 40, 60.9%). Urinary retention after catheter removal developed in 8 (12%) of 66 patients. There was no difference between the two groups in terms of the need for re-catheterization (14% vs. 10%, p: 0.63). All the patients who required re-catheterization (n: 8) and were discharged with a urinary catheter (n: 4) were male. When the male and female patients were evaluated separately, there was no difference in urinary retention in the early or late groups. Conclusions: Early or late removal of the catheter does not play a role in the development of urinary retention in patients undergoing rectal cancer surgery. Keywords: Rectal cancer. Catheter. Catheter removal time. Pelvic surgery.

Objetivo: Comparar los resultados de la retirada precoz y tardía de la sonda urinaria tras la cirugía de cáncer rectal. Método: Estudio prospectivo aleatorizado que incluyó pacientes sometidos a cirugía de cáncer rectal en un único centro. El momento de la retirada de la sonda urinaria se aleatorizó y se dividió en dos grupos: primeras 48 horas y después de 48 horas. Se compararon las tasas de retención urinaria y de nueva cateterización entre los pacientes con retirada precoz y tardía de la sonda. Resultados: Se incluyeron 66 pacientes, con una mediana de edad de 60 años (31-88 años) y predominio del sexo masculino (n = 40, 60.9%). Se produjo retención urinaria tras la retirada de la sonda en 8 (12%). No hubo diferencias entre los dos grupos en cuanto a necesidad de nueva cateterización (14% frente a 10%, p = 0.63). Todos los pacientes que precisaron un nuevo cateterismo (n = 8) y fueron dados de alta con una sonda urinaria (n = 4) eran varones. Conclusiones: La retirada precoz o tardía de la sonda no influye en la aparición de retención urinaria en pacientes intervenidos de cáncer de recto. Palabras clave: Cáncer rectal. Catéter. Tiempo de retirada del catéter. Cirugía pélvica.
Comparación de la retirada precoz y tardía de la sonda urinaria tras la cirugía de cáncer rectal
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Catheter; Catheter removal time; Pelvic surgery; Rectal cancer; Cáncer rectal; Catéter; Tiempo de retirada del catéter; Cirugía pélvica